2011
DOI: 10.1007/s10571-011-9734-x
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution and Cell Type-Specific Subcellular Localization of Prothymosin Alpha in Brain

Abstract: Prothymosin alpha (ProTα) is an acidic nuclear protein implicated in several cellular functions including cell survival. ProTα is found in the central nervous system, but the regional and cell type-specific expression patterns are not known. In this study, our immunohistochemical analysis demonstrated that ProTα is expressed ubiquitously throughout adult brain with difference in the intensity of region-specific protein reactivity. Interestingly, the highest ProTα signals were observed in the brain regions rele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Secretion of C3 in ADEV‐IL‐1β therefore appears to be a mechanism by which inflammatory signals are propagated. PTMA is a highly acidic protein, that is, expressed both in the nucleus and cytosol of astrocytes (Halder & Ueda, ). Similar to C3, PTMA is also involved in propagation of inflammatory signals via its C‐terminal domain that stimulates pro‐inflammatory responses and cytokine expression through activation of toll like receptor 4 (Gusella, Teixeira, Aberg, Uversky, & Mosoian, ; Ioannou et al, ; Mosoian et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Secretion of C3 in ADEV‐IL‐1β therefore appears to be a mechanism by which inflammatory signals are propagated. PTMA is a highly acidic protein, that is, expressed both in the nucleus and cytosol of astrocytes (Halder & Ueda, ). Similar to C3, PTMA is also involved in propagation of inflammatory signals via its C‐terminal domain that stimulates pro‐inflammatory responses and cytokine expression through activation of toll like receptor 4 (Gusella, Teixeira, Aberg, Uversky, & Mosoian, ; Ioannou et al, ; Mosoian et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…This enzyme regulates the brain levels of homocysteine, an excitatory amino acid, protecting hippocampal neurons against oxidative stress [ 122 , 123 ]. Two VIPs are also involved in responses to stress: RPL6 whose gene product is ribosomal protein L6, a regulator of the HDM2 —p53 pathway in response to ribosomal stress [ 124 ]; and DTWD2 , coding for prothymosin alpha, a highly acidic nuclear protein of the alpha-thymosin family involved in response to oxidative stress and neuronal survival [ 125 ]. Finally, two hubs, C6orf25 and PNPLA7 , are also related to protective roles.…”
Section: Resultsmentioning
confidence: 99%
“…; Cameron and Glover ). Since strong ProTα signals were detected in the SGZ of the hippocampal DG (Halder and Ueda ), we hypothesize that ProTα has crucial roles in the regulation of anxiety‐related behaviors, learning/memory‐functions, and neurogenesis. In this study, we have generated and used ProTα knockout mice to test this hypothesis.…”
mentioning
confidence: 95%
“…However, characterizing the physiological roles of endogenous ProTα in the brain without stress remains elusive. We previously demonstrated that ProTα protein is ubiquitously expressed throughout the adult mouse brain (Halder and Ueda ). Moreover, strong ProTα signals were detected in the neuronal cells in some brain regions, specifically in the adult neurogenesis‐related areas including the subgranular zone (SGZ) in the dentate gyrus (DG) of the hippocampus, the subventricular zone, and the olfactory bulb (Olf), proposing the idea that ProTα is involved in adult neurogenesis (Halder and Ueda ).…”
mentioning
confidence: 99%
See 1 more Smart Citation